GE_GERICHTE P/10768/2012 vom 7. März 2014 - GE Cour de justice (2014)
PRÉSOMPTION D'INNOCENCE; MEURTRE; TENTATIVE(DROIT PÉNAL); INTENTION; FIXATION DE LA PEINE; CONCOURS D'INFRACTIONS | CEDH.6.2; Cst.32.1; CP.111; CP.22.1; CP.47.1; CP.49.1